Peran Mahasiswa dalam Kuliah Kerja Nyata di Kampung Mandopi Rimom Kabupaten Manokwari Provinsi Papua Barat: The Role of Students in Community Service Program in Mandopi Rimom Village, Manokwari Regency, West Papua Province - Lintob, Firman Fandy; Muhammad, Jeinudin; Herietrenggi, Obeth; Warfandu, Ruth Margaretha; Maryar, Junita; Sorbu, Lili Lea Venesia; Inden, Paskalina Clara; Manilet, Bhadariah Rimosan; Mahmud, Nurul Huda; Jamius Bin Stepanus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Community Service Program (CSP) is a form of manifestation of community service that is in line with the demands and realization of the Tridharma of Higher Education. It is hoped that through CSP, students will be able to utilize knowledge, analyze community conditions, and provide solutions to various problems (social, economic, health, and education) in villages especially. The CSP implementation method consists of 4 stages, namely the initial stage (literature study, location survey, and interviews), the planning stage, the implementation stage, and the monitoring and evaluation stage. The CSP activity which took place in Mandopi Rimom Village, Manokwari Regency was carried out for 36 days (24 June - 8 August 2022) involving 1 field supervisor and 9 students from different study programs. A total of 35 work/activity programs (wp) have been successfully implemented involving participation and cooperation from village residents, school officials, posyandu officers, district health services, and the LPPM of Papua University. The work programs cover 8 areas of activity, namely village administration (7 wp), education (5 wp), health (5 wp), environment (10 wp), religion (2 wp), agriculture (2 wp), animal husbandry (2 wp) and socio-cultural economics (2 wp). The KKN seminar was held on the 35th day to present the results of the activities as well as get appreciation and suggestions as recommendations for implementing KKN in the next period. The results of the work program, activity documentation, obstacles, and suggestions/recommendations are then prepared in the form of a report to be submitted to the university's LLPM.